2021
DOI: 10.7150/jca.53382
|View full text |Cite
|
Sign up to set email alerts
|

β-elemene enhances the antitumor activity of erlotinib by inducing apoptosis through AMPK and MAPK pathways in TKI-resistant H1975 lung cancer cells

Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) significantly improve the outcome of non-small-cell lung cancer (NSCLC) patients with EGFR mutations, however, most TKI-treated patients will develop resistance to TKIs. β-elemene, extracted from Curcuma aromatica Salisb., has been widely used to treat various malignant tumors, including TKI-resistant NSCLC, but, the effects and the molecular mechanisms remain unclear. In this study, the NCI-H1975 cell line harboring double mutations L85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Another important compound in M. nepalensis essential oil is β-elemene, a noncytotoxic broad-spectrum antitumor drug utilized in Chinese traditional medicine (TCM) for more than 20 years to treat various cancer types, including lung, gastric, cervical, breast, liver, and bladder cancers, etc., including tyrosine kinase inhibitor (TKI)-resistant non-small-cell lung cancer [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Apart from its anticancer activity, β-elemene also possesses antioxidative and anti-inflammatory activities [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important compound in M. nepalensis essential oil is β-elemene, a noncytotoxic broad-spectrum antitumor drug utilized in Chinese traditional medicine (TCM) for more than 20 years to treat various cancer types, including lung, gastric, cervical, breast, liver, and bladder cancers, etc., including tyrosine kinase inhibitor (TKI)-resistant non-small-cell lung cancer [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Apart from its anticancer activity, β-elemene also possesses antioxidative and anti-inflammatory activities [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the essential oil showed a cytotoxic effect on HL-7702 cells, with IC 50 values of 19.14 ± 0.63 μg/mL. The cytotoxic activity of M. nepalensis essential oil could be attributed to the above-mentioned main compounds, as their cytotoxic effects on numerous cell lines have been widely reported [ 24 , 25 , 26 , 27 , 28 , 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that β-Ele could modulate multiple molecular pathways such as ERK1/2, PI3K/Akt/mTOR, ROS-MPAK, JAK/STAT3 involved in carcinogenesis [ 22 , 23 , 30 ]. It is reported that JAK/STAT3 signaling pathway plays critical roles in progression of many human solid tumors such as breast cancer [ 31 ], ovarian cancer [ 32 ] and OSCC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that β-Ele could modulate multiple molecular pathways such as ERK1/2, PI3K/Akt/mTOR, ROS-MPAK, JAK/STAT3 involved in carcinogenesis [21,22,29]. It is reported that JAK/STAT3 signaling pathway plays critical roles in progression of many human solid tumors such as breast cancer [30], ovarian cancer [31] and OSCC [32].…”
Section: Discussionmentioning
confidence: 99%